Burden of care in schizophrenia: implication of psychopathology of the illness - Othman, Zahiruddin; Razali, Salleh Mohd (Malaysian Psychiatric Association, 2005)
The recent trend towards community psychiatry appears to have shifted much of the burden of care of the chronically mentally ill from the institutions to the family. The objective of this study was to assess the implication of psychopathology in forty five schizophrenic patients on burden experience by their primary caregivers. Patients' psychopathology was assessed using Positive and Negative Syndrome Scale (PANSS) and the burden on caregivers was measured using Burden on Family Interview Schedule (BFS). The prevalence of burden was extensive with 40% reported severe subjective burden. The greatest objective burden was treatment expenses affecting 35.6% of primary caregivers. Schizophrenic patients' psychopathology (particularly delusion, hostility and hallucinatory behaviour) was found to be significantly correlated with the amount of burden experienced by primary caregivers. Grandiosity and stereotyped thinking were the least burdensome symptoms imposed on the caregivers.